Coupling analysis and vibration control of vehicle vertical vibration and pitching vibration - Xiaojun Zou; Bao Zhang; Guodong Yin; Hongnan Wang (SN Applied Sciences, 2023)
Article highlights The coupling model of vehicle vertical vibration and pitching vibration is established, and the mechanism and key influencing factors of the coupling vibration are revealed. A test method for vehicle coupled vibration identification is presented. In order to reduce the coupling vibration of vehicle, the stiffness matching method and analysis process are presented.